The effects of PHB-g-MA types on the mechanical, thermal, morphological, structural, and rheological properties of polyhydroxybutyrate biopolymers - Al, Gulyaz; Aydemir, Deniz; Altuntas, Ertugrul; Aydemir, Deniz (Elsevier, 2024)
This study investigates the grafting of polyhydroxybutyrate (PHB) chains with maleic anhydride (MA) in concentrations ranging from 5 % to 10 % by weight. This process was conducted during microwave treatment and using a reactive extruder, employing benzoyl peroxide (BPO) as the initiator. The impact of these methods on PHB's overall properties was thoroughly investigated. In the study, PHB-g-MA was incorporated into neat PHB via the extrusion process at a 5 % loading rate. Notably, the mechanical properties exhibited an increase in the presence of PHB-g-MA, likely due to morphological improvements in the neat PHB, as indicated by morphological characterization. X-ray diffraction results indicated crystallinity percentages increase with the addition of MA. Differential scanning calorimetry revealed minimal variation in melting and crystallization temperatures when PHB-g-MA was included. Both storage and loss moduli were enhanced by the incorporation of PHB-g-MA, and the blends exhibited consistent tan delta values. Regarding rheological properties, the storage and loss moduli of PHB blends containing PHB-g-MA blends were observed to rise with rising frequency values. Based on these results, the microwave process was identified as the most effective method for grafting.
Keywords: Biopolymers; Polyhydroxybutyrates; Phb Copolymers; Grafting Methods; Microwave Process